Quantitative Fluorescence Measurement of Cardiac Na+/Ca2+ Exchanger Inhibition by Kinetic Analysis in Stably Transfected HEK293 Cells - Namekata Iyuki; Kawanishi Toru; Iida-Tanaka Naoko; Tanaka Hikaru; Shigenobu Koki (Elsevier, 2006)
Abstract.: We developed a method to quantitatively evaluate the potency of Na+/Ca2+ exchanger (NCX) inhibitors with fluorescence microscopy in NCX1-transfected HEK 293 cells. The reverse mode and forward mode NCX activities were measured as the ascending slope of the early phase increase in cytoplasmic Ca2+ concentration after change to low Na+ extracellular solution and the descending rate (inverse of the exponential time constant) on return to normal solution, respectively. Both modes of NCX were inhibited by SEA0400 (2-[4-[(2,5-difluorophenyl)methoxy]phenoxy]-5-ethoxyaniline) and KB-R7943 (2-[2-[4-(4-nitrobenzyloxy)phenyl]ethyl]isothiourea methanesulfonate), and the concentration-inhibition relationships for both inhibitors were in good agreement with those previously reported in voltage clamped cardiomyocytes. Keywords:: Na+/Ca2+ exchanger, fluorescence microscopy, SEA0400